Biopolymer encapsulation for improved probiotic delivery: Advancements and challenges - Srirengaraj Vijayaram; Reshma Sinha; Caterina Faggio; Einar Ringø; Chi-Chung Chou (AIMS Microbiology)
Probiotics, known for their health benefits as living microorganisms, hold significant importance across various fields, including agriculture, aquaculture, nutraceuticals, and pharmaceuticals. Optimal delivery and storage of probiotic cells are essential to maximize their effectiveness. Biopolymers, derived from living sources, plants, animals, and microbes, offer a natural solution to enhance probiotic capabilities and they possess distinctive qualities such as stability, flexibility, biocompatibility, sustainability, biodegradability, and antibacterial properties, making them ideal for probiotic applications. These characteristics create optimal environments for the swift and precisely targeted delivery of probiotic cells that surpass the effectiveness of unencapsulated probiotic cells. Various encapsulation techniques using diverse biopolymers are employed for this purpose. These techniques are not limited to spray drying, emulsion, extrusion, spray freeze drying, layer by layer, ionic gelation, complex coacervation, vibration technology, electrospinning, phase separation, sol-gel encapsulation, spray cooling, fluidized, air suspension coating, compression coating, co-crystallization coating, cyclodextrin inclusion, rotating disk, and solvent evaporation methods. This review addresses the latest advancements in probiotic encapsulation materials and techniques, bridging gaps in our understanding of biopolymer-based encapsulation systems. Specifically, we address the limitations of current encapsulation methods in maintaining probiotic viability under extreme environmental conditions and the need for more targeted and efficient delivery mechanisms. Focusing on the interactions between biopolymers and probiotics reveals how customized encapsulation approaches can enhance probiotic stability, survival, and functionality. Through detailed comparative analysis of the effectiveness of various encapsulation methods, we identify key strategies for optimizing probiotic deployment in challenging conditions such as high-temperature processing, acidic environments, and gastrointestinal transit. The findings presented in this review highlight the superior performance of novel encapsulation methods using biopolymer blends and advanced technologies like electrospinning and layer-by-layer assembly, which provide enhanced protection and controlled release of probiotics by offering insights into the development of more robust encapsulation systems that ensure the sustained viability and bioavailability of probiotics, thus advancing their application across multiple industries. In conclusion, this paper provides the foundation for future research to refine encapsulation techniques to overcome the challenges of probiotic delivery in clinical and commercial settings.